Effect of red and blue light versus white light on fruit biomass radiation-use efficiency in dwarf tomatoes - Ke, Xinglin; Yoshida, Hideo; Hikosaka, Shoko; Goto, Eiji (Frontiers in Plant Science, 2024)
The effect of the ratio of red and blue light on fruit biomass radiation-use efficiency (FBRUE) in dwarf tomatoes has not been well studied. Additionally, whether white light offers a greater advantage in improving radiation-use efficiency (RUE) and FBRUE over red and blue light under LED light remains unknown. In this study, two dwarf tomato cultivars (‘Micro-Tom’ and ‘Rejina’) were cultivated in three red-blue light treatments (monochromatic red light, red/blue light ratio = 9, and red/blue light ratio = 3) and a white light treatment at the same photosynthetic photon flux density of 300 μmol m–2 s–1. The results evidently demonstrated that the red and blue light had an effect on FBRUE by affecting RUE rather than the fraction of dry mass partitioned into fruits (Ffruits). The monochromatic red light increased specific leaf area, reflectance, and transmittance of leaves but decreased the absorptance and photosynthetic rate, ultimately resulting in the lowest RUE, which induced the lowest FBRUE among all treatments. A higher proportion of blue light (up to 25%) led to a higher photosynthetic rate, resulting in a higher RUE and FBRUE in the three red-blue light treatments. Compared with red and blue light, white light increased RUE by 0.09–0.38 g mol−1 and FBRUE by 0.14–0.25 g mol−1. Moreover, white light improved the Ffruits in ‘Rejina’ and Brix of fruits in ‘Micro-Tom’ and both effects were cultivar-specific. In conclusion, white light may have greater potential than mixed red and blue light for enhancing the dwarf tomato FBRUE during their reproductive growth stage.